For Whom the Bell Tolls - Hemingway, Ernest, 1899-1961 (London Jonathan Cape, 1958)
After a young American is injured while blowing up a bridge behind enemy lines in the Spanish Civil War, he waits alone with a submachine gun for the enemy's approach
Keywords: Spain -- Civil War (Spain : 1936-1939)